Transfer technologii w Polsce na przykładzie spółek odpryskowych wywodzących się z instytutów badawczych i naukowych - Osuch-Rak, Ewa (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
Technology transfer plays a key role in boosting innovation in the economy. Spin off and spin out companies are important elements of the whole technology transfer system. Their goal is to develop and commercialize innovative technologies. The paper focuses on the processes of technology transfer in Poland, in which spin offs and spin outs, especially from scientific and research institutes, are involved. Part one deals with theoretical issues which are related to the definition of technology transfer, its main forms and channels. The second part presents main characteristics of spin offs and spin outs in Poland. Part three discusses the results of the research and concludes about the key conditions and motives behind spin o>s and spin outs in Poland